Visual Recovery Following Linezolid Cessation in an MDR-TB Patient: Detailed Case Analysis - Yovil Bagas Wiyana; Isnin Anang Marhana; Gatot Suhartono; Andreas Haryono (Case Reports in Pulmonology)
Multidrug-resistant tuberculosis (MDR-TB) is characterized by resistance to at least isoniazid and rifampicin. Linezolid is an antibiotic used for drug-resistant Gram-positive bacteria and is a treatment option for MDR-TB. However, its use is associated with optic neuropathy, presenting as acute worsening and bilateral vision loss, typically within 4 months of therapy. A 47-year-old male with MDR-TB relapsed during the sixth month of an individualized treatment regimen at Dr. Soetomo General Academic Hospital, Surabaya. The patient presented with weakness and anemia, receiving a regimen including levofloxacin (750 mg), linezolid (600 mg), clofazimine (100 mg), and cycloserine (500 mg). In the ninth month, the patient developed visual disturbances, initially suspected to be caused by an intracranial tumor. Despite various examinations and treatments, there was no improvement until linezolid was discontinued. The patient’s visual complaints gradually improved following the cessation of linezolid therapy. This case underscores the potential for linezolid to cause optic neuropathy during prolonged treatment for MDR-TB. Detailed ophthalmologic examinations, including optical coherence tomography (OCT) and magnetic resonance imaging (MRI), confirmed optic neuropathy without intracranial pathology. Despite high-dose steroid therapy, the patient’s vision improved only after 1 month since discontinuing linezolid. This highlights the importance of monitoring for ocular toxicity in patients undergoing long-term linezolid therapy and suggests that timely intervention can prevent permanent visual impairment. The case demonstrates the reversible nature of linezolid-induced optic neuropathy upon drug cessation and emphasizes the need for regular ophthalmologic assessments in patients receiving prolonged linezolid treatment. This report contributes to the understanding of the adverse effects of linezolid and underscores the importance of vigilant monitoring and alternative therapeutic strategies for MDR-TB.